UPAYA EDUKASI UNTUK BERADAPTASI PADA KEBIJAKAN NEW NORMAL DAN MENINGKATKAN IMUNITAS TUBUH SELAMA PANDEMI COVID-19 MELALUI KEGIATAN SEMINAR ONLINE - Akmal Yusuf Haryadi; Azzahra Novita Dewi; Dannis Pradana; James Ricardo; Mela Salsabilah; Muhammad Ariq Syahputra; Pradipta Arum Faustina; Sindy Nur Erwine Putri; Tasya Nadia; Tsalsa Fiorentina (Universitas Airlangga, 2020)
The purpose of the 230 KKN BBM group activity period 62 is to educate and prepare the public in facing and responding to the Covid-19 pandemic. Our method is to create two online seminar sessions, where in the first online seminar session the topic we raised was about